Shape Effect of Fractures on Intensity and Density of Discreet Fracture Networks - Esmaeilzadeh, Akbar; Shahriar, Kourosh (Periodica Polytechnica Civil Engineering, 2019)
Fractures are amongst the most important factors determining the behavior of rock masses. The lack of direct access to the real fractures’ distribution leads to the use of indirect methods for their study. The generation of the discrete fracture network is one of the most common indirect methods. Fractures’ shape is one of the most important properties that the simulation of which is of great help in studying the fracture network. A wide range of shapes which include from infinite plates to elliptical shape have been suggested for the simulation of fractures. The present paper makes use of the data collected from the pumped-storage power plant and dam project in Roudbar, Lorestan Province, to provide circular and elliptical network of discrete fractures; moreover, the parameters as density, intensity and the real mean value of the length of the fracture traces have been used to evaluate the effect and accuracy of the selected shapes. Following the implementation of the proposed method, it was made clear that the elliptical discrete fracture network, with a mean error value of 13.5 %, outperforms the circular disk discrete fracture network, with a mean error value of 27.5 %; hence, it was found providing more accurate results for the description of the fractures network in the aforementioned region.